Modelling Groundwater Flow and Contaminant Migration in Heterogeneous Fractured Media at a Municipal Solid Waste Landfill in Nanjing Lishui, China - Xiaochang Sun; Yin Jiang; Yong Huang; Yue Su; Kehan Miao (Geofluids)
The migration of groundwater flow and contaminants in fractured medium is complicated owing to the strong heterogeneity and anisotropy of fractured rock mass. Taking the environmental restoration and groundwater protection of the Lishui domestic waste landfill in Nanjing as the background, the groundwater environmental impact assessment and prediction are conducted for the groundwater environmental pollution that may be caused by the leakage of the landfill leachate after the closure of the domestic waste landfill. The strata of the landfill site are clay-cobble gravel, strongly and moderately weathered breccia, with obvious anisotropy and significant differences in rock mass permeability. A 3D numerical model of groundwater flow and contaminant migration in the landfill area is established by integrating the hydrogeological field tests and a conceptual model in the study area. Based on the parametric inversion method, the heterogeneous anisotropic permeability coefficient of the fractured medium is calibrated, and the temporal and spatial migration characteristics of contaminants such as ammonia nitrogen and mercury are predicted using the corrected model under the normal and failure conditions of the antiseepage curtain. The calculated results show that when the antiseepage fails, the maximum migration distances of contaminants in the horizontal direction after 100 days in the old and new landfills are 7.66 m and 15.64 m, respectively, and the maximum migration distances after 20 years are 192.5 m and 113.89 m, respectively. The migration direction and distances of contaminants are consistent with the hydrogeological conditions of the study area. The model calculation results provide a corresponding basis for the antiseepage control of contaminants.